UJI KUALITATIF KANDUNGAN FORMALIN PADA JAJANAN ANAK SEKOLAH DI KECAMATAN TASIKMADU KABUPATEN KARANGANYAR, JAWA TENGAH - Karyantina, Merkuria -; Kurniawati, Linda -; Harimurti, Fadjar - (Joglo, 2012)
ABSTRACTLately, we occured food product like tofu, meat ball, noodle and other junkfood for children with chemicals dangeruos, so people must be carefull toconsume that food. The food ubtainable sorrounding in schoolchild by grocer.That food was not durable, so we must add food preservative. A kind of foodpreservative is formaldehyde. Formaldehyde is a chemichal, but is’t in use forfood.This research to obtain qualitative utilization formaldehyde, on junk foodfor schoolchild on Elementary school in Tasikmadu district, Karanganyar.Sample comprised chicken nougat, meat ball, noodle, meat sausage and fish ball.Chemical for analysis are Kalium Permanganat (PK).Result shown that 45% junk food detected positive with formadehyde (forqualitative analysis), totaly sample are 60. 55% not detect negative withformaldehyde. Qualitative analysis with PK. Chicken nougat, meat ball, sausageand noodle are most junk food which sold in front of school by grocer. Main ofingredient are mixed of fluor and meat/chicken/fish for flavored. That food isdurable so that need food additive to preservative that food.Keyword : formaldehyde, junk food, schoolchild